"The Percption of secondary school pupiles of classroom management patterns and class problems in the mathématics teacher's share in secondary education -Acase study of Blida’s Secondary schoolFull name of the first author 1, Full name of the - allik, namiaa; kerkouche, fatiha (Journal of Social Sciences and Humanities, 2025)
The present study aims to investigate the types of class administration and class problems that exist in secondary schools in Blida, in terms of pupils’ perspectives. We used the descriptive method, and we drew a sample that contains 310 pupils (156: male, 154: female). To reach the objectives of the study we adopted tests to gather data such as: The first test is based on( 29) questions and three dimensions that are: authoritative type, democratic type and noisy type. The second test contains (36) questions and four dimensions: knowledge problems, ethic problems, performance and organizational problems. After that, we analysed data and we discussed the results in the following way: according to pupils’ perspectives, the dominant type among mathematic teachers is the democratic type. Whereas, the class problems faced by the pupils are based on knowledge and scientific issues.